Sensitization of nociceptors and dorsal horn neurons contributes to pain in sickle cell disease. (13th July 2019) - Uhelski, Megan L.; Simone, Donald A.
Highlights: Pain in sickle cell disease (SCD) can be severe and difficult to treat. Sensitization of both nociceptors and dorsal horn neurons contribute to pain in SCD. Targeting the processes the underlie sensitization in SCD may identify novel approaches for effective pain management in patients with SCD. Abstract: Sickle cell disease (SCD) describes a group of disorders associated with a point mutation in the beta chain of hemoglobin. The mutation leads to the creation of sickle hemoglobin (HbS) and causes distortion of erythrocytes through polymerization under low oxygen, resulting in characteristic sickle red blood cells. Vaso-occlusion episodes caused by accumulation of sRBCs results in ischemia-reperfusion injury, reduced oxygen supply to organs, oxidative stress, organ damage and severe pain that often requires hospitalization and opioid treatment. Further, many patients suffer from chronic pain, including hypersensitivity to heat and cold stimuli. Progress towards the development of novel strategies for both acute and chronic pain in patients with SCD has been impeded by a lack of understanding the mechanisms underlying pain in SCD. The purpose of this review is to highlight evidence for the contribution of peripheral and central sensitization that leads to widespread, chronic pain and hyperalgesia. Targeting the mechanisms that initiate and maintain sensitization in SCD might offer effective approaches to manage the severe and debilitating pain associated with this condition.